Italia ed Europa centro-orientale tra Medioevo ed Età moderna Economia, Società, Cultura - Fara, Andrea (Online-Schriften des DHI Rom. Neue Reihe - Pubblicazioni online del DHI Roma. Nuova serie, 2022)
It appears reductive to define the historical processes that characterised central and eastern Europe in medieval and modern times as a deviation or involution from the starting point of the western European model and outcomes, or as patent backwardness of the former compared to the latter. The most recent research moves beyond a dualistic view of the political, economic and social fortunes of the two parts of the continent. Comparative studies can highlight not only the similarities, but also the peculiarities that defined political, economic and social relations in medieval and modern Europe. This book presents recent research, focusing on several territories and their economic, social and cultural relations with the Italian Peninsula, and offers thought-provoking new insights.